In Vitro and Ex Vivo Evaluation of Zinc Peroxide Nanoparticles in Gel for Their Application as Intracanal Medication in Endodontics - Iván Olivares-Acosta; Lilian Romero-Sánchez; Marco Felipe Salas Orozco; Nuria Patiño Marín (Journal of Nanotechnology)
Conclusion: ZnO2NP gels exhibited greater antimicrobial activity compared to AgNPs and Ca(OH)2, suggesting their potential as an alternative intracanal medication in endodontics.